2017
DOI: 10.1017/s1355617717001011
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Dimensions of Depression and Apathy and Their Relationship With Cognition in Parkinson’s Disease

Abstract: Findings suggest that specific mood symptoms are associated with delayed verbal memory and executive function performance in non-demented patients with PD. Further research is needed to better understand possible mechanisms through which specific symptom dimensions of depression and apathy are associated with cognition in PD. (JINS, 2018, 24, 269-282).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 96 publications
2
16
0
2
Order By: Relevance
“…We excluded participants under 50 years of age ( N = 53) and non-PD controls. We excluded participants under 50 years of age because the relationship between mood symptoms and cognitive functioning is hypothesized to be driven by similar mechanisms (i.e., disruption of similar neural circuits; Butterfield et al, 2010; Jones et al, 2016; Pirogovsky-Turk et al, 2017; Szymkowicz et al, 2018; Varanese et al, 2011); however there is evidence that young onset-PD patients (before the age of 50) experience greater psychosocial stressors (loss of employment, perceived stigma, family disruptions), which may contribute to depressive symptoms (Schrag, Hovris, Morley, Quinn, & Jahanshahi, 2003). Therefore, we excluded participants under 50 to remove the possible confound that depression is differentially driven by separate mechanisms (i.e., psychosocial contributors vs. neurobiological contributors).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded participants under 50 years of age ( N = 53) and non-PD controls. We excluded participants under 50 years of age because the relationship between mood symptoms and cognitive functioning is hypothesized to be driven by similar mechanisms (i.e., disruption of similar neural circuits; Butterfield et al, 2010; Jones et al, 2016; Pirogovsky-Turk et al, 2017; Szymkowicz et al, 2018; Varanese et al, 2011); however there is evidence that young onset-PD patients (before the age of 50) experience greater psychosocial stressors (loss of employment, perceived stigma, family disruptions), which may contribute to depressive symptoms (Schrag, Hovris, Morley, Quinn, & Jahanshahi, 2003). Therefore, we excluded participants under 50 to remove the possible confound that depression is differentially driven by separate mechanisms (i.e., psychosocial contributors vs. neurobiological contributors).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding apathy and depression, at least five past studies have examined the relationship−intersectionality between apathy, depression, and cognition in PD (Butterfield, Cimino, Oelke, Hauser, & Sanchez-Ramos, 2010; Jones et al, 2016; Pirogovsky-Turk et al, 2017; Szymkowicz, Dotson, Jones, Okun, & Bowers, 2018; Varanese, Perfetti, Ghilardi, & Di Rocco, 2011). However, findings concerning whether cognition has a stronger relationship with apathy or depression have generally been inconsistent.…”
mentioning
confidence: 99%
“…A previous study reported that, while depressed patients showed significantly worse health status, low health literacy itself did not predict depressive symptomology [42]. Thus, it is crucial to disentangle the exact aspects of depression and its related factors that influence HRQoL, especially with regard to different subfactors such as loss of interest, apathy/lack of motivation, and somatic symptoms [43,44]. As it was the primary aim of the present analysis to understand how medication knowledge is related to HRQoL and which overall factors influence this relationship, the available data cannot provide information on the exact parameters of depressive mood that drive this influence.…”
Section: Discussionmentioning
confidence: 99%
“…The issue is further complicated by the fact that some overlap exists between depression and cognitive impairment [44,45]. Depression, a common nonmotor symptom observed in patients with PD, can cause reversible cognitive impairment, particularly poorer concentration, impaired memory, and impaired problem solving, without the additional presence of dementia [46].…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies have suggested that the presence of Lewy body and/or Alzheimer's pathology in these patients may lead to errors in memory encoding and retrieval [38]. Additional research is needed to definitively establish the relationship between apathy, depression, and cognitive impairment [40].…”
Section: Discussionmentioning
confidence: 99%